Iran petroleum contract (IPC) - a new generation of oil contracts - F. Hadavimoghaddam; M. M. Gortani (Russian Journal of Economics and Law)
Objective: to estimate the new generation of contracts (IPC, IOC) in the initial sector of oil industry and to compare them with previos contracts of other types used by the global producers in this sector.Methods: dialectical, comparative, descriptive, abstract-logical, and the method of system analysis.Results: in Iran of the post-sanctions period, the new model oil contracts (IPC) are becoming increasingly attractive to foreign investors. Under certain conditions, foreign oil company acquire the opportunity to reserve stocks, but foreign companies still cannot own oil deposits. One of the key advantages of the new contracts is the possibility to intensify development, search and optimal exploitation of oil and gas deposits, and to increase the coefficient of oil and gas extraction. The article presents a general characteristics of the new oil contracts, identifies the key spheres of their application. The key problems are systematized, related to the previous buy-back regime, which are either concealed in the new contract model, or information is insufficient for complete comprehension of the supposed risk distribution, such as the issues of buyback, commercialization, management, etc. The main advantages of the new integrated oil contracts are identified, such as: cost reimbursement, more complicated price structure, and transition to the model of a joint venture, as well as the advantages of the new contracts compared to buy-back contracts.Scientific novelty: the article presents a comparative analysis of the new integrated oil contracts in Iran and buyback contracts, and systematizes the key advantages and disadvantages of the new contracts.Practical significance: the research results can be used in scientific and academic activity of universities, as well as by state authorities when elaborating state policy in the sphere of oil production and processing.